Asthma in aquatic athletes - Mountjoy, M.; Fitch, K.; Kouidri, M. (coachesinfo.com)
Asthma is a common condition in aquatic sports. The incidence of asthma in swimmers and synchronized swimmers during the Beijing Olympic Games was 20%. Knowledge of the causes and triggers for asthma can help to decrease the incidence of asthma complications. The correct diagnosis of asthma is essential to ensure optimal care. There are many treatments for asthma which range from control of environmental triggers to inhaled and systemic (oral/intravenous) medications. The use of asthma medications is closely regulated by FINA and the World Anti-Doping Agency as some may have the potential to enhance performance at high doses and others may result in unfavourable side-effects. Knowledge of the regulations for asthma medication use is important to prevent a positive doping control test. This article reviews these features and addresses specific concerns for aquatic athletes.